Model Ketimpangan Pembangunan Ekonomi di Indonesia - Raharti, Rini; Laras, Titi; Oktavianti, Oktavianti (Jurnal Samudra Ekonomi dan Bisnis, 2021)
The purpose of this study is to analyze the effect of economic growth on the level of development inequality between provinces in Indonesia. The research method used is multiple linear regression analysis with OLS (ordinary least squares). The results of the analysis show that the inequality of economic development between provinces in Indonesia in 2005-2019 is relatively high because every year there is a significant increase, this fact is in line with the Neoclassical theory. Economic growth, poverty rate and population have a positive effect on inequality in economic development. The policy implication is that the provincial government in Indonesia should pay attention to sectors that absorb labor as a contribution to the level of economic growth and empower small communities.